Peningkatan Motivasi Siswa Kelas V pada Pembelajaran IPA melalui Model Explicit Instruction di Sekolah Dasar - Nurhelfi Risman Dani (Pedagogi: Jurnal Ilmu Pendidikan, 2019)
This study aimed to describe the increase in student motivation, by using the model of Explicit Instruction. This is a classroom action research with a sample of 21 students. The research instrument used is an observation sheet for student motivation, an observation sheet for teaching activities, a questionnaire sheet for students. The research results show an average student motivation observations on the first cycle indicators of students questioned 30.83 and 51.66 students answer questions. While students work together in a group discussion an average of 62.77. In the second cycle increased as follows: students ask 73.80 and answer questions 80.95. While the average student work together in a group discussion increased to 88.97. From the results of this study concluded that learning science with the model Explicit Instruction increase student motivation. Explicit Instruction suggested models can be used in science teaching in SD Negeri 19 Painan Selatan.